The BTK Inhibitor Ibrutinib (PCI-32765) Blocks Hairy Cell Leukaemia Survival, Proliferation and BCR Signalling: A New Therapeutic Approach - Sivina, Mariela (2014)
B cell receptor (BCR) signalling plays a critical role in the progression of several B-cell malignancies, but its role in hairy cell leukaemia (HCL) is ambiguous. Bruton tyrosine kinase (BTK), a key player in BCR signalling, migration and adhesion, can be targeted with ibrutinib, a selective, irreversible BTK inhibitor. We analysed BTK expression and function in HCL and analysed the effects of ibrutinib on HCL cells. We demonstrated uniform BTK protein expression in HCL cells. Ibrutinib significantly inhibited HCL proliferation and cell cycle progression. Accordingly, ibrutinib also reduced HCL cell survival after BCR triggering with anti-immunoglobulins (A, G, and M) and abrogated the activation of kinases downstream of the BCR (PI3K and MAPK). Ibrutinib also inhibited BCR-dependent secretion of the chemokines CCL3 and CCL4 by HCL cells. Interestingly, ibrutinib inhibited CXCL12-induced signalling, a key pathway for bone marrow homing. Collectively, our data support the clinical development of ibrutinib in patients with HCL.